Gambaran Pengetahuan Remaja Tentang Penanganan Disminorea Secara Swamedikasi (Self Care) - Neny Yuli Susanti Neny Yuli Susanti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2022)
Menstruation is one of the early characteristic changes in adolescents. Menstruation is a physiological condition, but it can cause complaints during menstruation, complaints often arise such as lower abdominal pain, irregular menstruation, low back pain which is commonly called dysmenorrhea. One of the actions that can be taken to treat dysmenorrhea is to increase adolescent knowledge about dysmenorrhea and its non-pharmacological and pharmacological treatment. This study aims to measure the knowledge of young women about dysmenorrhea treatment. This study used a descriptive method with a cross approach. This research was conducted by collecting data through a research questionnaire. The sample of this study were 96 young women aged 12 to 17 years. Sampling used purposive sampling. The results of the research based on descriptive analysis found that the highest level of respondents' knowledge about the definition of menstrual pain was 100%, while the lowest level of knowledge was about therapy for menstrual pain both pharmacologically and non-pharmacologically, namely the statement Herbal medicine by drinking herbs can reduce menstrual pain.